Die Krise der Wirtschaft: Auch eine Krise der Wirtschaftswissenschaften? - Gebhard Kirchgassner (Center for Research in Economics, Management and the Arts (CREMA), 2009)
Is the economic and financial crisis also a crisis of Economics? From different perspectives, today there is rather harsh criticism of Economics as a Social Science. In this paper, first, some of the recent failures of Economics are discussed. Then some of the criticisms are taken up that are less convincing, in particular criticisms of the application of the economic model of behaviour, the mathematisation of Economics and the principle of value freedom. The ap-propriate role of the government as well as of competition is discussed, and also which other consequences should be drawn for Economics as a science but also for economic policy. Fi-nally, we debate whether there is, besides the economic crisis, really as crisis of Economics as well.
Keywords: A10; H10; 330; Economic Crisis; Financial Crisis; Economic Theory; Role of the Govern-ment; Mathematics; Value Freedom; Pension System